Farinha de batata doce na dieta de frangos de corte e sua influência sobre aspectos anatômicos, fisiológicos e produtivos. - Nunes, Juliana Klug (2010)
A study was run to evaluate the partial replacement of corn by sweet potato meal, with or without supplementation of enzymes, in broiler diets from 1 to 47 days of age. A total of 150 day-old male broiler chicks were distributed in 30 pens of metallic batteries. A complete experimental block design in 3 x 2 experimental factorial arrangement was used (0, 20 and 40% of sweet potato meal and 0 and 200 g/ton of enzyme complex) with a total of 5 experimentals units per treatment (pen with 5 birds). Feed intake, body weight, feed conversion, and factor of efficiency rate and uniformity were evaluated at 14, 21 and 28 days of age. At that same age, 5 birds per treatment were sacrificed by cervical dislocation to evaluate allometric development of heart, liver, proventriculus and gizzard and the biometry of duodenum jejunum, ileum, ceca and rectum-colon. From 15 to 17 days of age, feed intake, weight gain, wet excreta weight, fecal moisture content, dry matter, crude protein, crude fiber, éter extract, ash, calcium and phosphorus of the excreta were recorded. After 28 days, the remaining birds were reallocated on in 6 floor pens. At 39 and at 47 days of age, carcass traits, organ allometry and intestinal biometry were evaluated the 3 birds per treatment. The variables were subjected to analysis of variance for main effects the sweet potato meal and enzyme, followed by splitting into levels of o the factor sweet potato meal into polinomial components. Results indicated that the replacement of corn by sweet potato meal, with or without enzyme complex addition, have not improved the productive performance of the broilers, adverselly affected carcass traits, allometry of organs, intestinal biometry and digestibility; and had a negative effect on body weight at 14, 21 and 28 days of age of the birds. The enzyme complex used has not altered the variables examined.